Sewer Sediment Bacterial Communities Suggest Potential to Transform Persistent Organic Pollutants. (1st December 2018) - Krumins, Valdis; Sun, Weimin; Guo, Jia; Capozzi, Staci; Fennell, Donna E.; Rodenburg, Lisa A.
ABSTRACT: Sediments of combined sewers are seeded with microbes from a variety of sources, and experience varying biogeochemical conditions. A variety of redox processes have been demonstrated to occur within sewer systems, as well as transformation of several recalcitrant xenobiotic contaminants. Illumina sequencing of the 16S ribosomal RNA gene from sediments of three combined sewer systems in the northeastern United States resulted in 10 000 to 47 000 operational taxonomic units per sample. Whereas orders Clostridiales and Bacteroidales, considered human fecal indicators, were dominant in one city's sediments; other cities had communities suggestive of diverse redox processes, including reductive dechlorination of chlorinated organic compounds. Collection systems previously associated with polychlorinated biphenyl (PCB) biotransformation, and those with elevated in situ PCB concentrations, had high abundances of Dehalococcoidetes. The results suggest that wastewater collection systems have intrinsic passive treatment capacity, reducing contaminant loads on water resource recovery facilities and, ultimately, on receiving waters.